Peningkatan Kemampuan Membaca Huruf Hijaiyah dengan Media Kartu Bergambar pada Kelompok A RA Al-Hidayah Kesamben - Siti Rohmatul Ummah; Mira Shodiqoh (Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
This study aims to determine the ability to read hijaiyah letters in early childhood before using card media with hijaiyah letters, the ability to read hijayah letters for early childhood after using hijaiyah printed card media and the efforts to improve reading Al-hijaiyah letters using picture card media in early childhood group A RA Al-Hidayah. This research uses Classroom Action Research by using 2 cycles of stages with the stages of planning, implementing, observing and reflecting. The instruments in this study were observation and documentation. Data analysis used qualitative descriptive with an individual completeness formula of 65% and grade completeness 85%.